Coastal resilience could be enhanced by co-interventions and synergistic Nature-based SolutionsThe data set is deposited online in Mendeley Data: Filz P. Literature review data: - Paulina Filz; Rodrigo Beas-Luna; Luca Rindi; Julio Lorda; Jan Freiwald; Luis Malpica-Cruz (Nature-Based Solutions, 2025)
Human activities and climate change drive the degradation of marine ecosystems, which provide essential services such as carbon sequestration, coastal protection, and fisheries. This loss amplifies societal challenges, including climate change mitigation, disaster risk reduction, and socio-economic vulnerability. Nature-based Solutions (NbS) offer a strategic approach to address these challenges by protecting, managing, and restoring coastal ecosystems, enhancing biodiversity and human well-being. Despite growing recognition of NbS, large-scale implementation remains hindered by funding constraints, policy integration barriers, and difficulty scaling effective strategies. Here, we present a systematic literature review investigating these factors in marine ecosystems to improve our understanding of investment motivations and co-interventions. We analyzed 39 case studies of NbS interventions and 32 studies on implementation opportunities and barriers. Our findings indicate that ecosystem restoration is the most prevalent NbS intervention in marine systems, often initiated in response to extreme climate events and disaster risk reduction. However, successful implementation frequently requires complementary strategies, such as income diversification, to reduce anthropogenic pressures and enhance livelihood resilience. Moreover, we identify synergies between addressing societal challenges and promoting ecosystem recovery, offering valuable insights for managers and researchers. To scale NbS effectively, barriers related to financing, policy integration, and technical expertise must be addressed. Our findings highlight the need for integrated, adaptive solutions linking ecological restoration with community-based management and sustainable economic development, ensuring resilience and social justice. Future research should explore innovative marine NbS approaches that support human well-being and acknowledge nature’s intrinsic value.